Leviticus: A Commentary for Biblical Preaching and Teaching - McKellar, Matthew (Southwestern journal of theology, 2025)
By Michael A. Harbin and Mark C. Biehl. Grand Rapids: Kregel Ministry, 2024, 464 pp., $ 24.99.